Morbidity pattern by age, sex and breed in insured cats in Japan (2008–2013). Issue 12 (December 2016) - Inoue, Mai; Hasegawa, Atsuhiko; Sugiura, Katsuaki
Objectives: The aim of the study was to describe the morbidity pattern of different diagnostic categories in insured cats in Japan by age, sex and breed. Methods: The annual incidence rates of having at least one insurance claim were calculated overall and stratified by diagnosis, age, sex and breed using data from insured cats in the period April 2008 to March 2013. Results: The overall annual incidence rate of having at least one insurance claim was 4632 (95% confidence interval 4608–4656) cats per 10, 000 cat-years at risk. The highest annual incidence rate was obtained for digestive system disorders, followed by urinary tract disorders and dermatological disorders. The incidence rates varied between breeds for most diagnostic categories: for cardiovascular system disorders, Scottish Fold, American Shorthair, Persian, Maine Coon, Norwegian Forest Cat, Ragdoll and Bengal had a higher annual incidence rate than crossbreeds. Conclusions and relevance: This study provides comparative and quantitative estimates of morbidity pattern in insured Japanese cats. These estimates can be utilised by veterinary practitioners, breeders and owners in diagnostic decision-making, breeding and when selecting a new pet, respectively.